EFIKASI BEBERAPA BAHAN PESTISIDA NABATI DALAM MENGENDALIKAN HAMA TANAMAN CABAI (Capsicum annum L.) - Hodiyah, Ida; Hartini, Elya (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2014)
The Red pepper is the one of horticulture commodity that has fluctuative high economic value. Myzus persica, Bactrocera spp. and Colletotrichum spp. are the major pests in red pepper, causing decreased quality and quantity of products. The aims of this experiments were to the develop integrated pest management of these pests, by utilization of botanical pesticides to control the pests. This experiment was arranged in randomized complete block design with five replicates. The treatments consisted of five levels, i.e: extraction of Jatropha curcas,Tinospora rumphii, Annona muricata and Toona sureni. The results showed that the botanical pesticides effective for controlling Aphids and Bactrocera spp. in seven weeks after plant. The botanical pesticide give the significant effect compare with control treatment. Extraction of Tinospora rumphii is the best efectivity for controlling Aphids (Myzus persicae). The botanical pesticide effective for controlling Aphids and Bactroceraspp. in seven weeks after plant. The extraction of Jatropha curcas and Toona sureni resulted the best efficacy to control the fruit flies (Bactrocera sp.).